Simple and selective method for determination of iodide in pharmaceutical products by flow injection analysis using the iodine-starch reaction - Nacapricha D. (2014)
This work exploited the well-known iodine-starch reaction for development of a simple flow-injection (FI) method for determination of iodide in pharmaceutical samples. Iodide in an injected zone was oxidized to iodine. A gas diffusion unit enables selective permeation of iodine through a hydrophobic membrane. Detection was made very selective for elemental iodine by employing formation of the I3--starch complex. The detection limit (3S/N) of the system was 1mgIL-1. For a liquid patent medicine used for asthma treatment we suggested modification of the system. Direct injection of this sample, which contains a particularly high concentration level of iodide (ca. 9000 mgIL-1), can be achieved by coupling a dialysis unit to the FI system. This has increased the working range to 6000-10,000 mgIL -1 without employing complicated nanoliter injection. © Springer-Verlag 2003.